1999
DOI: 10.1159/000054107
|View full text |Cite
|
Sign up to set email alerts
|

Modern Approach to Diagnosis in Patients with Suspected Deep Vein Thrombosis

Abstract: Deep vein thrombosis is a relatively common disease, amenable to therapy but with a potentially fatal outcome if untreated. The diagnosis can be made in most patients with the non-invasive imaging procedure ultrasonography, but limitations exist. As with all tests, there is a potential for false-positive and false-negative results. The latter are especially an issue for calf vein thrombi, and this in part has led to the concept of serial testing of the proximal venous system rather than imaging the calf. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Various studies have shown a high rate of limb salvage in these patients, who present with phlegmasia cerulea dolens. [13] Surgical thrombectomy is usually the last resort in patients with a high risk of hemorrhagic complications. However, results with surgical management are not satisfactory and incomplete thrombus removal, recurrent DVT and an increased incidence of systemic complications are known.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown a high rate of limb salvage in these patients, who present with phlegmasia cerulea dolens. [13] Surgical thrombectomy is usually the last resort in patients with a high risk of hemorrhagic complications. However, results with surgical management are not satisfactory and incomplete thrombus removal, recurrent DVT and an increased incidence of systemic complications are known.…”
Section: Discussionmentioning
confidence: 99%
“…Like DVT, clinical signs and symptoms of PE are both insensitive and nonspecific. To increase clinical accuracy in diagnosing PE, Wells developed a clinical estimation tool for establishing a patient's risk of PE on the basis of clinical signs and symptoms that is summarized in Table 3 [59‐63]. Once again, it would be rare for an acute inpatient rehabilitation patient to have a score of less than 2 and be in the low probability category.…”
Section: Vte Confirmationmentioning
confidence: 99%
“…38,43,44 The combination of clinical probability and the inclusion of plasma D-dimer measurement by a rapid ELISA method before US is probably the better strategy for the clinical suspicion of symptomatic DVT. 45 For the diagnosis of isolated symptomatic distal DVT, a meta-analysis of methodologically good quality studies reported the sensitivity of US to be only 73%. 46 In asymptomatic patients the sensitivity of both compression US and color Doppler US for the diagnosis of DVT is much lower than in symptomatic patients.…”
Section: Lower Limb Venous Compression Ultrasonography In Dvtmentioning
confidence: 99%